2020
DOI: 10.3390/ijerph17186502
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internet Use on Health Outcomes of Rural Adults: Evidence from China

Abstract: Health, as basic human capital, is quite important for rural adults. However, in China, the average level of public health facilities and services is far lower in rural areas than in cities. In recent years, the internet has developed rapidly in China, and is increasingly affecting rural adults in a positive way. The purpose of this paper is to reveal whether internet use can be an effective way to improve the health of rural adults. This study used three rounds of data from the China Family Panel Studies (CFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…In terms of education, There are significant differences between the effects that internet use has on the health of people with different education levels. The Internet has a positive association with the health of people with high education levels compared to those with low education levels, and this finding is consistent with the results of the study by Li and Peng [58,59]. This is because more educated people have less difficulty using the Internet, are good at using Internet tools to obtain health knowledge, and have a better level of health knowledge, whereas less educated people may find it difficult to use the Internet.…”
Section: Summary Of the Findingsupporting
confidence: 89%
“…In terms of education, There are significant differences between the effects that internet use has on the health of people with different education levels. The Internet has a positive association with the health of people with high education levels compared to those with low education levels, and this finding is consistent with the results of the study by Li and Peng [58,59]. This is because more educated people have less difficulty using the Internet, are good at using Internet tools to obtain health knowledge, and have a better level of health knowledge, whereas less educated people may find it difficult to use the Internet.…”
Section: Summary Of the Findingsupporting
confidence: 89%
“…Li found that Internet use demonstrated significant positive effects on the health of rural adults through a survey of 7528 rural residents aged >16 years in China. They also found that adults improved their health by increasing social interaction and staying physically active through the Internet [ 14 ]. Lyu studied 7193 older adults aged 60–95 years and found that Internet use was positively associated with the self-assessed health of older adults, while social capital was an important mediator of this relationship [ 15 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…where IV ct was our instrumental variable (IV), and the other variables were defined as above. We examined whether the respondent had a computer at home and considered this as the IV, which is widely used as an instrumental variable for the Internet [39].…”
Section: Handling Endogeneity Issuesmentioning
confidence: 99%